Influence of Domain-General Abilities and Prior Division Competence on Fifth-Graders’ Fraction Understanding - Stelzer, Florencia (2019)
The present study analyzed the relationship between domain-general abilities and fraction knowledge in fifth grade, and investigated the mediating role of division competence in that relationship. Children (n = 175) were assessed in fourth grade on domain-general abilities (selective attention, working memory, fluid intelligence) and on division competence; and in fifth grade on fraction conceptual knowledge. Mediation analyses revealed that domain general abilities were direct predictors of fraction concepts, and division competence mediates the 32% of the effect of working memory and the 17% of the effect of intelligence on fraction knowledge. These findings support the assumptions of those theoretical models of numerical cognition that proposed a central role of general cognitive abilities for mathematics learning and indicate that there are distinct pathways from general cognitive abilities to fraction conceptual knowledge.